2021
DOI: 10.1002/chem.202100922
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure‐Property Relationship Modelling for the Prediction of Singlet Oxygen Generation by Heavy‐Atom‐Free BODIPY Photosensitizers**

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 126 publications
0
26
0
Order By: Relevance
“…The singlet oxygen quantification is an excellent tool to probe the triplet manifold of chromophoric systems . Highly reactive and prevalent singlet oxygen finds application in photodynamic therapeutic purposes since it kills the tumorous or diseased cells. , During the singlet oxygen quantification analysis, the triplet excitation energy of Se-PBI ( 3* Se-PBI ; photosensitizer) is transferred to ground-state (triplet) oxygen ( 3 Σ g ), resulting in singlet oxygen ( 1 Δ g ) generation. The singlet oxygen quantum yield, = 73.8% for Se-PBI, is one of the remarkable values reported among the modified PBI derivatives (Table S2 and Figure S13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The singlet oxygen quantification is an excellent tool to probe the triplet manifold of chromophoric systems . Highly reactive and prevalent singlet oxygen finds application in photodynamic therapeutic purposes since it kills the tumorous or diseased cells. , During the singlet oxygen quantification analysis, the triplet excitation energy of Se-PBI ( 3* Se-PBI ; photosensitizer) is transferred to ground-state (triplet) oxygen ( 3 Σ g ), resulting in singlet oxygen ( 1 Δ g ) generation. The singlet oxygen quantum yield, = 73.8% for Se-PBI, is one of the remarkable values reported among the modified PBI derivatives (Table S2 and Figure S13).…”
Section: Resultsmentioning
confidence: 99%
“…The 1 O 2 quantum yields ( ) of the photosensitizers were calculated with Rose Bengal (RB) as a standard ( = 0.80 in methanol). , The absorbance of the 1 O 2 scavenger 1,3-diphenylisobenzofuran (DPBF) was adjusted to be around 1.0 in aerated dimethylformamide (DMF). Then, a photosensitizer ( Se-PBI ) was added to the cuvette, and the absorbance of the photosensitizer was adjusted to be around 0.2–0.3.…”
Section: Methodsmentioning
confidence: 99%
“…36 Although predicting the efficiency of SOCT for a given structure in different media is still challenging, recently, we performed the first quantitative structure-property relationship (QSPR) study of these systems and developed a method for predicting singlet oxygen generation quantum yields for heavyatom-free BODIPYs in different solvents based on a combination of quantum mechanical molecular descriptors and topological descriptors. 37 QSPR analysis showed that structures containing a higher number of electron donor/acceptor subunits, e.g., donor-acceptor-donor (D-A-D) and acceptor-donor-acceptor triads, in general exhibit less pronounced solvent dependence of triplet state formation compared to D-A dyads. Such triads have been actively studied as materials for photovoltaics 38 and it has been demonstrated that intramolecular charge transfer (ICT) in these systems is faster than in D-A dyads.…”
Section: Introductionmentioning
confidence: 99%
“…Except for BODIPYs, it is therefore still unclear whether these complexes have any potential as photosensitizers for PDT. An example of a new research direction is investigating the possibility of enhancement triplet generation in AlDIPYs and other p-block mono(dipyrrinato) complexes by using similar techniques as developed for BODIPY's such as structural modifications [232]. Due to their similarity, tuning the photophysical properties tris(dipyrrinato) complexes with Ga(III) and In(III) metal ions is expected to be possible in an identical way as has been done for bis(dipyrrinato)Zn(II) complexes.…”
Section: Future Prospectsmentioning
confidence: 99%